Reversing metabolic dysregulation in farnesoid X receptor knockout mice via gut microbiota modulation - Ines Leila Paraiso; Armando Alcazar Magaña; Alexandra Alexiev; Thomas J. Sharpton; Claudia S. Maier; Chrissa Kioussi; Jan F. Stevens (PLoS ONE, 2025)
The farnesoid X receptor (FXR), expressed in the liver and in the small intestine, is a key regulator of glucose and lipid metabolism. Its pharmacological modulation is explored as a potential treatment for obesity-related metabolic impairments. To develop effective pharmacological interventions, it is crucial to differentiate the individual contributions of intestinal and hepatic FXR to lipid metabolism. This study aimed to evaluate the impact of intestinal FXR ablation on gut microbiome composition and metabolic potential in high-fat diet (HFD)-fed mice. Additionally, we determined the genotype-specific effects of xanthohumol, a hop-derived ligand of FXR, known to mitigate metabolic dysfunction in HFD-fed mice. Intestinal FXR knockout prevented diet-induced obesity, a phenotype that correlated with a decrease in the predicted functional capacity of the gut microbiome. Intestinal FXR deficiency resulted in increased abundances of bacteria producing secondary bile acids, such as Oscillospira, and a decrease in beneficial bacteria, such as Akkermansia, both of which were mitigated by xanthohumol. Our findings provide insights to understand the contribution of intestinal FXR and gut microbiome to metabolic regulation under HFD conditions. We underscore the ability of xanthohumol to restore homeostasis, highlighting its potential to improve gut health.